Short and Long term outcomes from Percutaneous Endoscopic Gastrostomy with Jejunal Extension - Ridtitid, Wiriyaporn (Surg Endosc, 2016)
BACKGROUND: There is a paucity of data regarding the safety and efficacy of PEG-J. We evaluated adverse events related to percutaneous endoscopic gastrostomy with jejunal extension (PEG-J) and determined the clinical impact of PEG-J in those with chronic pancreatitis (CP). METHODS: This cohort study included all patients who underwent PEG-J placement in a tertiary-care academic medical center between 2010–2012. Main outcome measurements were 1) short- and long-term complications related to PEG-J; 2) changes in weight and hospitalizations during the 12-month period before and after PEG-J in the CP subgroup. RESULTS: Of 102 patients undergoing PEG-J placement, the overall technical success rate was 97%. During a median follow-up period of 22 months (1–46 months, n=90), at least one tube malfunction occurred in 52/90 (58%; 177 episodes) after a median of 53 days (3–350 days), requiring a median of 2 tube replacements. Short-term (<30 days) tube malfunction occurred in 28/90 (31%) and delayed in 24/90 (27%); these included dislodgement (29%), clogging (26%) and kinking (14%). In the CP subgroup (n=58), mean body weight (kg) (70 vs. 71, p=0.06) and body mass index (kg/m(2), 26 vs. 27, p=0.05) increased post-PEG-J. Mean number of hospitalizations (5 vs. 2, p<0.0001) and inpatient days per 12 months (22 vs. 12, p=0.005) decreased. CONCLUSIONS: While we observed no major complications related to PEG-J, half of patients had at least one episode of tube malfunction. In the CP subgroup, jejunal feeding via PEG-J significantly reduced the number of hospitalizations and inpatients days, while improving nutritional parameters.